2006
DOI: 10.1242/jcs.03046
|View full text |Cite
|
Sign up to set email alerts
|

Novel function of β-arrestin2 in the nucleus of mature spermatozoa

Abstract: A growing number of proteins originally found in endocytic structures of the plasma membrane appear to be able to traffic into the nucleus, but the cellular function of this translocation remains unclear. We have found that β-arrestin2, which typically shows a cytoplasmic localization owing to constitutive nuclear export, appears in the nucleus after stimulation of the G-protein-coupled odorant receptor hOR17-4. In the nucleus, β-arrestin2 was involved in transcriptional regulation as shown by a Gal4-based tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 46 publications
6
52
0
Order By: Relevance
“…Arr3 is predominantly found out of the nucleus due to the presence of its two-leucine nuclear export signal (45). However, Neuhaus et al (46) reported Arr3 to be localized in the nucleus of HEK293 cells and mature spermatozoa. COX-1 is located in the endoplasmic reticulum and perinuclear membranes, whereas COX-2 resides predominantly in the perinuclear envelope (47).…”
Section: Pgds (Data Not Shown) Strong Growth Was Also Observed On Trpmentioning
confidence: 99%
“…Arr3 is predominantly found out of the nucleus due to the presence of its two-leucine nuclear export signal (45). However, Neuhaus et al (46) reported Arr3 to be localized in the nucleus of HEK293 cells and mature spermatozoa. COX-1 is located in the endoplasmic reticulum and perinuclear membranes, whereas COX-2 resides predominantly in the perinuclear envelope (47).…”
Section: Pgds (Data Not Shown) Strong Growth Was Also Observed On Trpmentioning
confidence: 99%
“…They showed that the nuclear translocation of ␤-arrestin 2 is dependent on receptor phosphorylation and clathrin-mediated receptor endocytosis. Their data indicate that odorant-receptor-induced nuclear localization of ␤-arrestin 2 might play a role in the regulation of gene expression during the early processes of fertilization (Neuhaus et al, 2006). Both ␤-arrestin 1 and ␤-arrestin 2 thus seem to serve as nuclear messengers for GPCRs.…”
Section: ␤-Arrestins As Nuclear Messengersmentioning
confidence: 99%
“…In addition, GPCRs can affect gene expression through the ␤-arrestin-dependent signaling mechanisms described above. Recent work, however, indicates that ␤-arrestins can affect gene expression more directly -by entering the nucleus Neuhaus et al, 2006). In human embryonic kidney 293, HeLa and osteosarcomal cells, ␤-arrestin 1 appears to be present in both the nucleus and the cytoplasm whereas ␤-arrestin 2 is cytoplasmic at steady state (Oakley et al, 2000;Scott et al, 2002;Wang et al, 2003b).…”
Section: ␤-Arrestins As Nuclear Messengersmentioning
confidence: 99%
See 1 more Smart Citation
“…Although b-arrestin2 usually displays a cytoplasmic distribution caused by constitutive nuclear export, 36 it also undergoes active nuclear import and has been shown to accumulate in the nucleus after stimulation of the odorant GPCR hOR17-4 in spermatozoa. 37 In these cells, the nuclear accumulation of b-arrestin2 may be implicated in the control of gene expression during the early steps of fertilization. It is therefore possible that the translocation of b-arrestin2 to the CD34 1 cell nucleus regulates some of the For personal use only.…”
Section: Linmentioning
confidence: 99%